Fasting and Mental Health: An Interdisciplinary Study - Sya’roni Alfajri; Dedi Sukma (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
Fasting as a spiritual and health practice has been practiced for thousands of years in various religious and cultural traditions around the world. In the last decade, researchers have shown increasing interest in the health aspects of fasting, not only from a physiological but also a psychological perspective. This phenomenon is interesting to study further, especially in the context of modern society which often faces stress, anxiety, and various mental disorders. The approach used in this study was a qualitative approach with a literature study method that analyzed in depth various reference sources related to the mental impact of fasting. The results of the review of several studies show that fasting has been proven to have an effect on mental health because it has a significant impact on overall mood improvements, with reduced anxiety levels and increased feelings of calm. Furthermore, another important aspect of mental health is cognitive function, which includes attention, concentration, memory, and executive function. It was found that cognitive alertness is generally maintained during short- to medium-term fasting, but begins to decline after longer fasting durations. Fasting also has an impact on extraordinary psychological resilience and good mental health despite advanced age. Researchers attribute this extraordinary mental resilience to the consistent practice of long-term fasting, which may have induced significant neuroplastic and psychological adaptations.